Revisiting Pāṇini's generative power - Lowe, JJ (De Gruyter, 2021)
In this paper I revisit recent claims that Pāṇini’s generative grammar has fully context-sensitive power. I show that in fact Pāṇini assumed acyclicity as a constraint on rule application, limiting the power of his superficially context-sensitive formalism in a way entirely parallel to much work in modern phonology.